Translating the Histone Code - Jenuwein, Thomas; Allis, C. David (Science (American Association for the Advancement of Science), 2001)
Chromatin, the physiological template of all eukaryotic genetic information, is subject to a diverse array of posttranslational modifications that largely impinge on histone amino termini, thereby regulating access to the underlying DNA. Distinct histone amino-terminal modifications can generate synergistic or antagonistic interaction affinities for chromatin-associated proteins, which in turn dictate dynamic transitions between transcriptionally active or transcriptionally silent chromatin states. The combinatorial nature of histone amino-terminal modifications thus reveals a "histone code" that considerably extends the information potential of the genetic code. We propose that this epigenetic marking system represents a fundamental regulatory mechanism that has an impact on most, if not all, chromatin-templated processes, with far-reaching consequences for cell fate decisions and both normal and pathological development.